The Categorisation of Society and the Treatment of Zimmis in the Early History of Islam (Khairulummah, 2023)
Zimmis, non-Muslim subjects of the Islamic polity, were liable to pay a capitulation tax or jizya. The Holy Prophet (SAW) established good relations with Jews and Christians but preferred the expulsion of Jews from Madina. Governors like Walid bin Uqba and Amir Muawia demonstrated religious tolerance towards Christians. During Hisham bin Abdul Malik's reign, zimmi were granted full religious liberty, but Umayyad governors were less liberal and subjected them to persecution. Governorial policies towards non-converts were harsh, with the adoption of the Arabic language in financial jargon and an Arabic coinage system.